Amplification of obliquity forcing through mean annual and seasonal atmospheric feedbacks - S.-Y. Lee; C. J. Poulsen (Copernicus Publications, 2008)
Pleistocene benthic δ 18 O records exhibit strong spectral power at ~41 kyr, indicating that global ice volume has been modulated by Earth's axial tilt. This feature, and weak spectral power in the precessional band, has been attributed to the influence of obliquity on mean annual and seasonal insolation gradients at high latitudes. In this study, we use a coupled ocean-atmosphere general circulation model to quantify changes in continental snowfall associated with mean annual and seasonal insolation forcing due to a change in obliquity. Our model results indicate that insolation changes associated with a decrease in obliquity amplify continental snowfall in three ways: (1) Local reductions in air temperature enhance precipitation as snowfall. (2) An intensification of the winter meridional insolation gradient strengthens zonal circulation (e.g. the Aleutian low), promoting greater vapor transport from ocean to land and snow precipitation. (3) An increase in the summer meridional insolation gradient enhances summer eddy activity, increasing vapor transport to high-latitude regions. In our experiments, a decrease in obliquity leads to an annual snowfall increase of 25.0 cm; just over one-half of this response (14.1 cm) is attributed to seasonal changes in insolation. Our results indicate that the role of insolation gradients is important in amplifying the relatively weak insolation forcing due to a change in obliquity. Nonetheless, the total snowfall response to obliquity is similar to that due to a shift in Earth's precession, suggesting that obliquity forcing alone can not account for the spectral characteristics of the ice-volume record.